Intervention Programs to Promote the Quality of Caregiver–Child Interactions in Childcare: A Systematic Literature Review - Benedetta Ragni (MDPI AG, 2021)
Sensitive caregiver–child interactions appear fundamental throughout childhood, supporting infants’ wellbeing and development not only in a familial context but in professional caregiving as well. The main aim of this review was to examine the existing literature about Early Childhood Education Context (ECEC) intervention studies dedicated to caregiver–child interaction, fostering children’s socioemotional developmental pathways. Studies published between January 2007 and July 2021 were identified in four electronic databases following PRIMSA guidelines. The initial search yielded a total of 342 records. Among them, 48 studies were fully reviewed. Finally, 18 of them met all inclusion criteria and formed the basis for this review. Main factors characterizing implemented programs were recorded (e.g., intervention and sample characteristics, dimensions of the teacher–child interaction targeted by the intervention, outcome variables, main results) in order to frame key elements of ECE intervention programs. Our review points to a range of fundamental issues that should consider to enhance ECEC interventions’ efficacy, supporting children’s socioemotional development and caregiver–child interaction. Reflections and considerations for future research are provided.